2020
DOI: 10.1002/ppp.2083
|View full text |Cite
|
Sign up to set email alerts
|

A characteristic periglacial landform: Automated recognition and delineation of cryoplanation terraces in eastern Beringia

Abstract: Automated recognition and delineation of specific landforms and their constituent elements ranks among the most active areas of contemporary geomorphological research. This study contributes to that literature by applying semi‐ and fully automated recognition procedures to upland periglacial geomorphic landscapes. The Cryoplanation Terrace semi‐Automated Recognition (CTAR) algorithm utilizes basic terrain parameters to identify locations of cryoplanation terraces (CTs) from the high‐resolution ArcticDEM. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Such terraces consist of gently sloping treads and steep risers cut into bedrock and tend to form benchlike staircases that dominate certain hillslopes. 18,180 The terraces are particularly well developed in unglaciated highlands of Beringia and show similar regional trends in elevation to cirques from the last major glaciation. 181 Some field evidence suggests that cryoplanation terraces develop through locally intensified weathering and mass wasting associated with late-lying snow patches (nivation).…”
Section: The Efficacy Of Frost-driven Processesmentioning
confidence: 86%
See 3 more Smart Citations
“…Such terraces consist of gently sloping treads and steep risers cut into bedrock and tend to form benchlike staircases that dominate certain hillslopes. 18,180 The terraces are particularly well developed in unglaciated highlands of Beringia and show similar regional trends in elevation to cirques from the last major glaciation. 181 Some field evidence suggests that cryoplanation terraces develop through locally intensified weathering and mass wasting associated with late-lying snow patches (nivation).…”
Section: The Efficacy Of Frost-driven Processesmentioning
confidence: 86%
“…Third, there is growing evidence that frost action can contribute towards a characteristic periglacial landscape formed by erosion of cryoplanation terraces in uplands. Such terraces consist of gently sloping treads and steep risers cut into bedrock and tend to form bench‐like staircases that dominate certain hillslopes 18,180 . The terraces are particularly well developed in unglaciated highlands of Beringia and show similar regional trends in elevation to cirques from the last major glaciation 181 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevation of the lower terrace tread is 1,150 m a.s.l. Reger 8 reported that the area of cryoplanation terrace treads in interior and western Alaska ranges from 3,000 to 819,000 m 2 (also see 9,10 ) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%